A phase 2 trial of induction nab‐paclitaxel and cetuximab given with cisplatin and 5‐fluorouracil followed by concurrent cisplatin and radiation for locally advanced squamous cell carcinoma of the head and neck12. Issue 4 (18th September 2012) - Adkins, Douglas; Ley, Jessica; Trinkaus, Kathryn; Thorstad, Wade; Lewis, James; Wildes, Tanya; Siegel, Barry A.; Dehdashti, Farrokh; Gay, Hiram; Mehan, Paul; Nussenbaum, Brian
Abstract BACKGROUND: Complete response (CR) at the primary tumor site as assessed by clinical examination following induction chemotherapy with PF (cisplatin and 5‐fluorouracil [5‐FU]) is a favorable predictive factor for overall survival and disease control in patients with locally advanced squamous cell carcinoma of the head and neck. In most series, the rate of CR at the primary site after induction PF was 20% to 30%. This study evaluated the efficacy and feasibility of induction nab‐paclitaxel and cetuximab given with PF (ACPF) followed by definitive chemoradiation (CRT) in a phase 2 trial. METHODS: Patients with squamous cell carcinoma of the head and neck were treated with ACPF (nab‐paclitaxel 100 mg/m2/week; cetuximab 250 mg/m2/week; cisplatin 75 mg/m2 on day 1; 5‐FU 750 mg/m2/day on days 1 through 3) every 21 days for 3 cycles followed by CRT (cisplatin 100 mg/m2 on days 1, 22, and 43 of radiation therapy [RT]). CR at the primary tumor site after 2 cycles of ACPF was the primary endpoint. RESULTS: Thirty patients were enrolled, of which 22 (73%) had large (T3/T4) primary tumors. The CR rate at the primary tumor site after 2 cycles of ACPF was 53% and the overall response rate was 100%. Twenty‐nine (96%) patients completed 3 cycles of ACPF, 26 (90%) completed definitive RT per protocol, and 22 of the 27 evaluable patients (81%) received > 2 of the 3 planned doses of cisplatin with RT. The estimated 2‐year overall and progression‐free survival rates were 84% and 65%, respectively. CONCLUSIONS: Induction ACPF resulted in a high CR rate (53%) at the primary tumor site even in large tumors and did not adversely affect delivery of definitive CRT. Further investigation of ACPF is warranted. Cancer 2013. © 2012 American Cancer Society.